Pengaruh Variasi Komposisi Agregat Kasar Terhadap Kuat Tekan dan Penyerapan Air Paving Block - Dera Anggun Saputri; Syafri Wardi; Angelalia Roza (Yayasan Literasi Sains Indonesia, 2023)
According to SNI 03-0691-1996, paving block is a composition of building materials made from a mixture of portland cement or similar hydraulic adhesive materials, water and aggregate with or without other additives. Pavement construction in Indonesia mostly uses natural aggregates or crushed stone that has a rough and angular surface so that it has excellent adhesion to the concrete. The purpose of this study is to evaluate the effect of the addition of crushed stone on the compressive strength and water absorption of concrete paving blocks, compared with paving blocks of mortar. Paving block test samples were made with 5 variations of composition of cement:sand:crushed stone, namely 1:4:0, 1:4:1, 1:4:2, 1:4:3 and 1:4:4. Each composition was made as test samples of blocks with a size of 20 cm × 10 cm × 6 cm. The test results showed that the average compressive strength of paving blocks with the composition of 1:4:0, 1:4:1 and 1:4:4 was less than 8,5 MPa and water absorption is greater than 10%; thus, they were not classified as paving blocks with grade D. While, the paving blocks with the composition of 1:4:2 and 1:4:3 were classified as paving blocks with grade D.